The Influence of Work Motivation and Compensation on the Performance of Service Division Employees: Study At A Car Company In Bandung - Bagus Septian Hidayat; Dedi Hadian; Aan Hardiyana; Adhie Fasha Nurhadian (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study examines the impact of work motivation and compensation on the performance of employees in the service division of a car company in Bandung. Work motivation and remuneration are critical variables influencing employee performance in an organization, particularly in the service industry, which requires optimal productivity and service quality. The employed research method is a descriptive analysis utilizing a quantitative methodology. Data were gathered by distributing questionnaires to personnel in the service division of the studied organization. The data analysis employed Pearson Product Moment correlation and coefficient of determination analysis with IBM SPSS Statistics software. The study's findings demonstrate that work motivation and compensation positively influence employee performance. A regression study demonstrates a robust correlation between job motivation and compensation for employee performance. This condition suggests that elevated job motivation and an improved remuneration structure will significantly enhance employee performance. The study’s results indicate that job motivation has a more significant impact on employee performance than compensation. Both aspects concurrently contribute significantly to enhancing employee performance. These findings underscore organizations' need to prioritize work-motivating aspects and offer equitable and competitive remuneration to enhance employee performance. This study's conclusions can inform the development of firm policies that enhance employee performance through improved human resource management practices. By recognizing the significance of job motivation and remuneration, corporate management is anticipated to cultivate a supportive work environment, foster excitement, and enhance staff productivity within the automotive service sector.